Sosialisasi Masyarakat Tentang Manajemen Pemenuhan Kebutuhan Nutrisi Pada Anak Usia 1- 2 Tahun - Firdaus Firdaus; Wesiana Heris Santy; Mustika Chasanatusy Syarifah; Rizki Kardina (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Nutritional status is important in pre-school children because at this time the brain really needs a supply of nutrients in its growth, but many problems arise in the nutritional status of pre-school children. Knowledge of maternal nutrition who cannot choose nutritious food will affect nutritional status which results in many toddlers being malnourished. This Community Service activity is carried out to improve nutrition and understanding of balanced nutrition and improve the status of children aged 1-2 years. Implementation of community service within 3 months. The method used is to increase knowledge to 32 mothers who have children aged 1-2 years, in RT 12 RW 02 Ds. Tebuwung, District. Shaman, Gresik. Knowledge of the use of the lecture method and the improvement of making additional food. The level of knowledge of the respondents can be known by conducting a pretest and posttest in the form of a questionnaire that will be filled out by the respondent. The results of the pretest of mother's knowledge about fulfilling nutritional needs obtained knowledge of 65% less, enough 27%, good 8%, after counseling and demonstration and results after knowledge lack of 0%, enough 15%, good 85%. According to Susilowati et al, 2017 Increased knowledge is accompanied by new behaviors in offering nutritious food for toddlers so that their nutritional status becomes good. Mother's knowledge is the main key to meeting the nutritional needs of children aged 1-2 years. Knowledge-based on understanding can also foster good new behaviors. Counseling and demonstrations are useful to increase the mother's knowledge in meeting needs.